Balancing Children's Rights to Information and Digital Protection: Implementation of Indonesian Government Regulation No. 17 of 2025 in Basic Education - Cunduk Wasiati; Edy Chrisjanto; Lintang Unggul Triharjun (Annpublisher, 2026)
Background. Social media's growth gives kids the chance to learn and access knowledge, but it also puts them at risk of exposure to content that is inappropriate for their age and developmental stage. To safeguard children when they use digital services, the Indonesian government enacted Government Regulation Number 17 of 2025 on the Governance of the Implementation of Electronic Systems in Child Protection. Purpose. To fulfill children's right to information through social media, this study examines the implications of implementing Government Regulation Number 17 of 2025, identifies barriers to its implementation, and assesses SD Negeri Kyai Mojo Yogyakarta's efforts to overcome these challenges. Method. The study employs a qualitative, descriptive methodology. The study used literature research, interviews, and documentation involving SD Negeri Kyai Mojo State Elementary School and the Yogyakarta City Education, Youth, and Sports Office to gather data. Through source triangulation and qualitative analysis, the validity of the data was examined. Results. The results show that SD Negeri Kyai Mojo has fulfilled children's right to obtain information through social media in a limited and proportionate manner by allowing gadget use when necessary to support learning. Schools also conduct conditional supervision and device inspections as a preventive measure against access to content that is not appropriate for children's age. Obstacles to implementing gadget restrictions mainly arise when students need to communicate with their parents because they left supplies behind, emergencies occur, or there are late pick-ups. These obstacles can be addressed by having classroom teachers serve as communication mediators and involving school officials to support communication between students and parents. Conclusion. The research concludes that implementing child protection policies in the digital space can go hand in hand with fulfilling children's rights to information if carried out proportionately through collaboration among schools, parents, and the government.